The development of ScanServe – smart QR-driven summons application for streamlined disciplinary case management: a step towards a smart campus / Wan Fariza Wan Abdul Rahman and Nur Athirah Su’aidah Abu Samah - Wan Abdul Rahman, Wan Fariza; Abu Samah, Nur Athirah Su’aidah (Universiti Teknologi MARA, Kedah, 2025)
To create a more efficient and technologically advanced campus environment, this paper presents the development of a Smart QR-Driven Summons Application for streamlined disciplinary case management. Leveraging the Mobile Application Development Life Cycle (MADLC) as the methodology, using Android Studio and Firebase, the system is designed to automate and enhance the traditional method of issuing and managing disciplinary summons within academic institutions. The proposed solution integrates Quick Response (QR) code technology, enabling the rapid generation, distribution, and tracking of summonses via mobile devices. This innovation not only reduces the administrative burden but also minimises errors associated with manual processes. A detailed system interface is presented to illustrate the application's functionalities and user experience. To evaluate the effectiveness and usability of the application, a System Usability Scale (SUS) test was conducted, yielding positive results that underscore the potential of the application in contributing to the development of a smart campus ecosystem. The findings demonstrate the application’s capability to improve operational efficiency and user satisfaction, marking a significant step towards the digital transformation of disciplinary processes in educational institutions.